Globalization, inequality and economic policy - Broll, Udo; Kemnitz, Alexander; Vivekananda Mukherjee (Economics and Business Review, 2019)
In our paper a very simple model is used to analyze the relationship betweentrade globalization, inequality and economic policy. Although the local governmentexclusively maximizes the welfare of the marginalized (unemployed) people, the inequalityof relative consumption between employed and unemployed will increase withintensified trade liberalization. In contrast to this result the relative income inequalitymay fall in certain situations.